Consequences of prosocial and antisocial behaviors in adolescent male soccer players: The moderating role of motivational climate - Al-Yaaribi, A.; Kavussanu, M. (Psychology of Sport and Exercise, 2018)
Objective: This study examined (a) whether prosocial and antisocial teammate behaviors are related to athletes` enjoyment, anger, effort, perceived performance, and commitment; (b) the mediating role of anger, enjoyment, and perceived performance on some of these relationships; and (c) whether any of these relationships are moderated by motivational climate. Design: Cross-sectional. Method: Adolescent male soccer players (N=358, M age=14.48yrs) completed questionnaires assessing the aforementioned variables. The results were analysed using structural equation modelling (EQS 6.1; Bentler, 2003). Results: Prosocial teammate behavior was positively related to effort, perceived performance, and commitment and these relationships were mediated by enjoyment. The relationships between prosocial teammate behavior and perceived performance and commitment were mediated by effort and perceived performance, respectively. In contrast, antisocial teammate behavior was positively related to anger and negatively related to effort and perceived performance. Mastery and performance climates moderated the relationships between prosocial and antisocial teammate behaviors and enjoyment as well as perceived performance, with a stronger relationship at higher levels of the climates. Conclusion: The findings highlight the potential consequences of prosocial and antisocial teammate behaviors and the importance of coach-created motivational climate in adolescents. Future research in sport should employ objective measures to capture actual teammate behaviors.